Investigating the Onion Skin Method for Solving Simple Linear Equations - Syahida Abdul Ghani; Masitah Shahrill; Hardimah Said (Southeast Asian Mathematics Education Journal)
As one of the mathematical mnemonic tactics that use a visual approach, the Onion Skin Method (OSM) compares the structure of an onion to that of a mathematical problem. The study aimed to determine, through pre-and post-testing, the influence of incorporating the OSM into the learning of solving basic linear equations. The sample involved two Year 10 classes consisting of 31 students. Using a paired t-test, the study demonstrated a considerable improvement in students’ ability to solve linear equations. A semi-structured interview with six students was done to examine their perceptions. Five themes were derived from the interviews: the time spent by students to solve simple linear equations, students’ reactions to their performance on the post-test, students’ preferred method for solving linear equations, students’ perception of the OSM, and students’ future use of the OSM. The findings indicated that the OSM accommodates the learning styles of the participants, which predominantly employ mnemonic strategies. This research may inspire teachers to use alternative methods when instructing students on solving fundamental linear equations, allowing them to modify their instruction or develop more practical lessons for teaching.